solve y – 2x = 3 and Y = 3x + 5 by substitution

Question

solve y – 2x = 3 and Y = 3x + 5 by substitution

in progress 0
Raelynn 1 week 2022-01-07T00:11:04+00:00 2 Answers 0 views 0

Answers ( )

    0
    2022-01-07T00:12:09+00:00

    Answer:

    x = -2

    Step-by-step explanation:

    y – 2x = 3, y = 3x + 5

    Substitute the value of y for y

    3x + 5 – 2x = 3

    Step 1: Simplify both sides of the equation

    3x + 5 − 2x = 3

    3x + 5 + −2x = 3

    (3x + −2x) + (5) = 3 (Combine Like Terms)

    x + 5 = 3

    x + 5 = 3

    Step 2: Subtract 5 from both sides

    x + 5 − 5 = 3 − 5

    x = −2

    0
    2022-01-07T00:12:37+00:00

    Answer:

    MATHPAPA

    its a website that gives you all the answers im being dead serious

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )